2018
DOI: 10.1093/inthealth/ihx068
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality and determinants of survival from cervical cancer in Northwest Russia: a registry-based cohort study

Abstract: Incidence of and mortality from cervical cancer in northwest Russia is considerably higher than in developed countries. Increased incidence in recent years may be attributed to increased screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…Patients who presented with advanced stage died more than those with early stage. This result is in line with the studies conducted in New Zealand [ 33 , 34 ]. The increment of mortality could be as the cancer stage getting advanced, its metastasis rate could be increased and these factors might decrease the probability to respond a treatment and lead to death [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients who presented with advanced stage died more than those with early stage. This result is in line with the studies conducted in New Zealand [ 33 , 34 ]. The increment of mortality could be as the cancer stage getting advanced, its metastasis rate could be increased and these factors might decrease the probability to respond a treatment and lead to death [ 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Women with FIGO stage IV and III were about 12 and 7.4 times at high risk to die as compared to those with early clinical stage I respectively. This finding is in line with the studies conducted at north west Russia (HR = 3.8, 95% CI 2.5 to 5.8) [18], Nigeria (HR = 3.3, 95% CI: 1.2–8.9) [26], Ethiopia (HR = 2.60 (95%CI: 1.67–4.04) [23] and North East India (HR =1.8,95% CI:1.2 to 2.7) [20]. The similarity of these findings may be due to the reason that as the cancer stage increases, metastasis will also increase, which leads to compromising of patient’s immunity to resist other infections, difficulty of treating such complicated metastasis cases and these factors in aggregate increases the probability of dying [13].…”
Section: Discussionsupporting
confidence: 92%
“…The current study demonstrated that, about 38.6% cervical cancer patients could survive at least 5 years after diagnosis of cervical cancer. This is significantly lower than the researches conducted in Brazil which were 84% [14], India 62% [15], Malaysia 71.1% [16],China 66.61% [17],Northwest Russia 60.0% [18],Mysuru (India) 48.1% [19], but in line with the study conducted in North East India 40.7% [20].…”
Section: Discussionsupporting
confidence: 65%
“…This can be explained by the limited cervical cancer early diagnosis practices and lack of awareness campaigns for Tanzanian women in preventing the occurrence of cervical cancer [ 6 10 ]. These challenges could be responsible for increased incidence and mortality rates of cervical cancer in older women [ 8 , 32 ]. Moreover, introduction of immunohistochemistry assessment of biomarkers may aid in the histopathological classification of cervical cancer and other cancers, and may also assist in early identification of Tanzanian women who are at high risk for recurrence of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%